Synthesis, Antibacterial Evaluation and Docking Study of Some New Fused Pyrido-Pyrimidine and Naphthyridine Cycles - Hamid H. Mohammed (Journal of Global Pharma Technology, 2016)
New fused pyrido-pyrimidine and naphthyridine cycles were synthesized and characterized using spectral analysis. Initially, 2-cyano-N-(1-phenylethylidene) acetohydrazide (2) was prepared from the reaction of cyanoacetic acid hydrazide (1) with acetophenone then cyclized to 4,6-diamino-2-oxo-1-((1-phenylethylidene)amino)-1,2-dihy-dropyridine-3-carbonitrile (3) by the action of malononitrile and triethyl amine in dioxin. Fused pyridopyrimidine cycles (4-6) were obtained from the reaction of compound 3 with formic acid, glacial acetic acid and propionic acid, respectively in the presence of POCl3 as a catalyst. The novel cycles (7-9) were synthesized from the cyclization reaction of compound 3 with benzoyl chloride, phenylisocyanate and phenylisothiocyanate in presence of pyridine. Naphthyridine cycles (10-13) were obtained by cyclization of compound 3 with some of aliphatic ketones namely; acetone, cyclohexanone, 2-butanone and 4-methyl-2-pentanone, respectively in presence of FeCl3 as catalyst. The antimicrobial activity of the synthesized derivatives was evaluated against several bacterial species as well as candida albicans. Docking study was also achieved to explore the binding affinity of the potent discovered hit (9) inside the binding pocket of glucosamine-6-phosphate synthase, a target enzyme for the antimicrobial agents.Keywords: Naphthyridine Cycles; Fused Pyrido-Pyrimidine; Antibacterial.